2005
DOI: 10.1111/j.1529-8817.2005.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Common CRP Gene Variants with CRP Levels and Cardiovascular Events

Abstract: SummaryC-reactive protein (CRP) is a well-documented marker of atherosclerotic cardiovascular disease risk. We resequenced CRP to identify a comprehensive set of common SNP variants, then studied and replicated their association with baseline CRP level among apparently healthy subjects in the Women's Health Study (WHS; n = 717), Pravastatin Inflammation/CRP Evaluation trial (PRINCE; n = 1,110) and Physicians' Health Study (PHS; n = 509) cohorts. The minor alleles of four SNPs were consistently associated in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
187
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(227 citation statements)
references
References 46 publications
35
187
3
1
Order By: Relevance
“…Although studies that assessed common variation and haplotypes in the CRP gene with plasma CRP levels have used different SNP selection and haplotype estimation methodologies, our study confirmed previous reports of the association of plasma CRP with genetic variants, especially that the minor alleles of rs1205 and rs1800947 are associated with lower CRP levels and that the minor allele of rs1130864 is associated with higher CRP levels. 12,[15][16][17]21 Moreover, we found that the G allele of rs2246469 was associated with lower CRP levels in Han Chinese.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although studies that assessed common variation and haplotypes in the CRP gene with plasma CRP levels have used different SNP selection and haplotype estimation methodologies, our study confirmed previous reports of the association of plasma CRP with genetic variants, especially that the minor alleles of rs1205 and rs1800947 are associated with lower CRP levels and that the minor allele of rs1130864 is associated with higher CRP levels. 12,[15][16][17]21 Moreover, we found that the G allele of rs2246469 was associated with lower CRP levels in Han Chinese.…”
Section: Discussionmentioning
confidence: 63%
“…Increased circulating concentrations of high-sensitivity CRP (hsCRP) have been associated with a panel of clinical endpoints, such as obesity, diabetes mellitus, 3-5 hypertension 2,6-8 and atherosclerotic cardiovascular disease. [9][10][11][12][13] The reported heritability estimates of CRP range from 27 to 40%. Common genetic variants in the CRP gene were found to be associated with plasma hsCRP levels, 11,[13][14][15][16] and this association may vary in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…The haplotype ACCCA and some of its alleles have previously been associated with low CRP levels in Finns (Eklund et al, 2008) as well as in other populations, (Carlson et al, 2005;Miller et al, 2005;Crawford et al, 2006;Suk Danik et al, 2006) although not all of the SNPs of the haplotypes used in these studies were exactly the same. According to a recent meta-analysis with well-adjusted CRP values, systemic CRP concentrations seem not to be associated with PC as such (Heikkila et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…However, our study represents an independent replication for the association of CRP polymorphisms with CRP levels (21,22,24). Independent replication studies in racially diverse CKD progression cohorts will be necessary to substantiate the new findings.…”
Section: Discussionmentioning
confidence: 92%